Criterios de hospitalización en recién nacidos con ictericia - Pesantez Yaguana, Brisila Mayrin (Machala : Universidad Técnica de Machala, 2022)
INTRODUCTION: Neonatal jaundice is a frequent pathology in our environment, characterized by yellow pigmentation of the skin and mucous membranes, it is classified into physiological and non- physiological jaundice, with physiological jaundice being the most frequent, with an overall prevalence of 60 % to 80% of newborns, the criteria for hospitalization are identification of risk determinants, signs of acute encephalopathy, total bilirubin levels, to carry out early detection and designate the pertinent treatment, avoiding kernicterus. OBJECTIVE: To determine the hospitalization criteria related to neonatal jaundice through a systematic bibliographic search of high-impact scientific articles, to apply them in the first level of care according to the guidelines established by the Ministry of Public Health of Ecuador and thereby sensitize staff of health on the adequate management of this pathology. METHODOLOGY: Descriptive, retrospective study obtained in bibliographic sources in PubMed, Scielo, Google academic, Elsevier published in the last 5 years and that contribute to the proposed topic. RESULTS: In relation to 34 scientific articles investigated where the criteria for hospitalization in the newborn with jaundice and updates on the appropriate approach to neonatal jaundice are specified. CONCLUSIONS: Hospitalization criteria related to neonatal jaundice are risk determinants, family history, gestational age <38 weeks, visible jaundice on the first day, exclusive breastfeeding, total bilirubin values, signs of acute encephalopathy. The same ones that are classified as high, medium and low risk.
INTRODUCCIÓN: La ictericia neonatal es una patología frecuente en nuestro medio, que se caracteriza por la pigmentación amarilla de la piel y mucosas, se clasifica en ictericia fisiológica y patológica, siendo la fisiológica la más frecuente, con una prevalencia global del 60% al 80% de recién nacidos, los criterios de hospitalización son la identificación de determinantes de riesgo, signos de encefalopatía aguda, niveles de bilirrubina total, con el objetivo de realizar la detección temprana y designar el tratamiento pertinente, evitando el Kernicterus. OBJETIVO: Determinar los criterios de hospitalización relacionados con la ictericia neonatal mediante la búsqueda bibliográfica sistematizada de artículos científicos de alto impacto, para aplicarlos en el primer nivel de atención según los lineamientos establecidos por el Ministerio de Salud Pública del Ecuador y con ello sensibilizar al personal de salud sobre el manejo adecuado de esta patología. METODOLOGÍA: Estudio descriptivo, retrospectivo obtenido de fuentes bibliográficas en PubMed, Scielo, Google Académico, publicados en los últimos 5 años y que contribuyen al tema planteado. RESULTADOS: En relación a 34 artículos científicos investigados donde se puntualiza los criterios de hospitalización en el recién nacido con ictericia y actualizaciones sobre el abordaje adecuado de ictericia neonatal. CONCLUSIÓN: Los criterios de hospitalización relacionados con ictericia neonatal son determinantes de riesgos, antecedentes familiares, edad gestacional < 38 semanas, ictericia visible en el primer día, lactancia materna exclusiva, valores de bilirrubina total, signos de encefalopatía aguda. Los mismo que están clasificados en riesgo alto, medio y bajo.
Keywords: ICTERICIA NEONATAL; FOTOTERAPIA; HOSPITALIZACION; HIPERBILIRRUBINEMIA